A Truncated Search Key Title Index - Philip L. Long; Frederick Kilgour (Information Technology and Libraries, 1972)
An experiment showing that 3, 1, 1, 1, search keys derived from titles are sufficiently specific to be an efficient computerized, interactive index to a file of 135,938 MARC II records.